El papel de la interacción significativa y las técnicas dramáticas en la educación de estudiantes con discapacidad visual en la UACh - Ortiz de Zárate, Amalia; Walper Gormáz, Katherina; Aros Muñoz, Pablo; Hidalgo Torres, Daniela; Siebert Hechenleitner, Francisca; Rojas, Julio (Colombian Applied Linguistics Journal, 2014)
This article informs about the development of the project entitled “Proposal and validation of active methodologies for the inclusion of students with visual impairment (SwVI, hereafter) in the first two years of college” (DEP 2012-01) at Universidad Austral de Chile. This project seeks to involve professors at UACh in the teaching process of students with special needs (SwSN): visual impairment, through a workshop of active methodologies and drama techniques in the different Departments, Schools and Centers of the institution in 2013 and 2014. First, the investigation methodology and the activities to be utilized in this project are specified. Then, this article presents the State of the Art related to inclusion in educational institutions and universities, the importance of meaningful interaction, and the teachers and students’ role in the learning process. Finally, the article shows the methodology developed in the framework of the project: the use of the senses, drama techniques, and the teaching proposal implemented in the awareness-raising workshops for the teaching of students with special needs.